\(B=3abc+a^2\left(a-b-c\right)+b^2\left(b-a-c\right)+c^2\left(c-a-b\right)-c\left(b-c...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 8 2019

Đặt \(f=a^2\left(a-b-c\right)+b^2\left(b-a-c\right)+c^2\left(c-a-b\right)\)

\(=3abc+a^3+b^3+c^3-a^2b-b^2a-a^2c-b^2c-c^2a-c^2b\)

\(=a^2\left(a-b\right)+b^2\left(b-a\right)+c\left[2ab-a^2-b^2+c\left(c^2-bc-ac+ab\right)\right]\)

\(=\left(a-b\right)\left(a^2-b^2\right)-c\left(a-b\right)^2+c\left(c-a\right)\left(c-b\right)\)

\(=\left(a-b\right)^2\left(a+b+c\right)+c\left(b-c\right)\left(a-c\right)\)

\(\Rightarrow BT=\left(a-b\right)^2\left(a+b+c\right)+c\left(b-c\right)\left(a-c\right)-c\left(b-c\right)\left(a-c\right)\)

\(=\left(a+b\right)^2\left(a+b+c\right)\)

19 tháng 7 2016

a)a(b2+c2)+b(a2+c2)+c(a2+b2)+2abc

=ab2+ac2+ba2+bc2+ca2+cb2+2abc

=(ab2+ba2)+(ac2+bc2)+(ca2+abc)+(cb2+abc)

=ab(a+b)+c2(a+b)+ca(a+b)+cb(a+b)

=(a+b)(ab+c2+ca+cb)

=(a+b)(a+c)(b+c)

b)a3-b3-c3-3abc

=(a-b)3-c3+3ab(a-b)-3abc

=(a-b-c)[(a-b)2+(a-b)c+c2]+3ab(a-b-c)

=(a-b-c)(a2-2ab+b2+ac-bc+c2+3ab)

=(a-b-c)(a2+b2+c2+ab-bc+ca)                            

a: \(\left(a^2-b^2\right)^2+\left(2ab\right)^2\)

\(=a^4-2a^2b^2+b^4+4a^2b^2\)

\(=a^4+2a^2b^2+b^4=\left(a^2+b^2\right)^2\)

b: \(\left(ac+bd\right)^2+\left(ad-bc\right)^2\)

\(=a^2c^2+b^2d^2+a^2d^2+b^2c^2\)

\(=c^2\left(a^2+b^2\right)+d^2\left(a^2+b^2\right)\)

\(=\left(a^2+b^2\right)\left(c^2+d^2\right)\)

c: \(\left(ax+b\right)^2+\left(a-bx\right)^2+c^2x^2\)

\(=a^2x^2+b^2+a^2+b^2x^2+c^2x^2\)

\(=a^2\left(x^2+1\right)+b^2\left(x^2+1\right)+c^2x^2\)

\(=\left(x^2+1\right)\left(a^2+b^2\right)+c^2x^2\)